2012
DOI: 10.1007/s10637-012-9851-5
|View full text |Cite
|
Sign up to set email alerts
|

The prostate cancer blocking potential of the histone deacetylase inhibitor LBH589 is not enhanced by the multi receptor tyrosine kinase inhibitor TKI258

Abstract: Pharmacologic options for patients with castration-resistant prostate cancer are limited. It has been suggested that targeting intracellular molecules, which have been altered during neoplastic development, may slow tumor growth. Therefore, the growth-blocking potential of the histone deacetylase-inhibitor LBH589 and the multiple tyrosine kinase-inhibitor TKI258, applied alone or in combination, was investigated in a panel of prostate cancer cell lines. PC-3, DU-145 or LNCaP cells were treated with various con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Compared with other anticancer drugs, HDAC inhibitors are well tole rated with a good toxicity profile (26). A number of studies have reported that LBH589 exerts antitumor effects on various cancer-derived cells, including epithelial ovarian, prostate and liver cancer cells, as well as hepatocellular carcinoma cells (27)(28)(29)(30). Nevertheless, the anticancer activities of LBH589 on human OSCC cells are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other anticancer drugs, HDAC inhibitors are well tole rated with a good toxicity profile (26). A number of studies have reported that LBH589 exerts antitumor effects on various cancer-derived cells, including epithelial ovarian, prostate and liver cancer cells, as well as hepatocellular carcinoma cells (27)(28)(29)(30). Nevertheless, the anticancer activities of LBH589 on human OSCC cells are not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated upregulation of the tumor suppressor proteins p21 and p27 after dovitinib treatment in cell culture models of prostate cancer(72). On the basis of findings in an AR-negative prostate cancer xenograft model that suggested a role for FGF/FGFR in osteoblastic progression of CRPC in bone (61), a phase 2 trial of dovitinib in patients with bone mCRPC is currently underway (ClinicalTrials.gov: NCT00831792).…”
Section: Fgf Pathway Inhibition In Prostate Cancermentioning
confidence: 99%
“…P rostate cancer is a prevalent cancer type worldwide that severely threatens men's health (Vallo et al, 2013;Siegel et al, 2014). Current therapies for prostate cancer have progressed considerably, but the disease remains intractable and is the second leading cause of cancer-related death (Siegel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%